The association between stress hyperglycemia and unfavorable outcomes in patients with anterior circulation stroke after mechanical thrombectomy - Zhang, Junrun; Dong, Dawei; Zeng, You; Yang, Bing; Li, Fangze; Chen, Xuefang; Lu, Jingchong; Guan, Min; He, Niu; Qiao, Hongyu; Li, Keshen; Xu, Anding; et al. (Frontiers in Aging Neuroscience, 2023)
Background and purpose Stress hyperglycemia is common in critical and severe diseases. However, few studies have examined the association between stress hyperglycemia and the functional outcomes of patients with anterior circulation stroke, after mechanical thrombectomy (MT), in different diabetes status. This study therefore aimed to determine the relationship between stress hyperglycemia and the risk of adverse neurological functional outcomes in anterior circulation stroke patients with and without diabetes after MT. Methods Data of 408 patients with acute anterior circulation stroke treated with MT through the green-channel treatment system for emergency stroke at the First Affiliated Hospital of Jinan University between January 2016 and December 2020 were reviewed retrospectively. The stress hyperglycemia ratio (SHR) was calculated as fasting plasma glucose (mmol/L) divided by glycosylated hemoglobin (%). The patients were stratified into four groups by quartiles of SHR (Q1-Q4). The primary outcome was an excellent (nondisabled) functional outcome at 3 months after admission (modified Rankin Scale score of 0–1). The relationship between stress hyperglycemia and neurological outcome after stroke was assessed using multivariate logistic regression. Results After adjusting for potential confounders, compared with patients in Q1, those in Q4 were less likely to have an excellent outcome at 3 months (odds ratio [OR], 0.32, 95% confidence interval [CI], 0.14–0.66, p = 0.003), a good outcome at 3 months (OR, 0.41, 95% CI, 0.20–0.84, p = 0.020), and major neurological improvement (OR, 0.38, 95% CI, 0.19–0.73, p = 0.004). Severe stress hyperglycemia increased risks of 3-months all-cause mortality (OR, 2.82, 95% CI, 1.09–8.29, p = 0.041) and ICH (OR, 2.54, 95% CI, 1.21–5.50, p = 0.015). Conclusion Stress hyperglycemia was associated with a reduced rate of excellent neurological outcomes, and increased mortality and ICH risks in patients with anterior circulation stroke after MT regardless of diabetes status.